Analisis Konsumsi Beras Organik Wilayah Perkotaan di Yogyakarta - Irene Kartika Eka Wijayanti; Retno Lantarsih; Sipri Paramita (Jurnal Dinamika Sosial Ekonomi, 2004)
The objectives of the research were (1) to know the effect of the organik rice characteristics on rice consumption, (2) to know the socio-economic factors that affect organik rice consumption on household level in city area of Yogyakarta. The research was conducted by discriptive method. Samples for organaic rice consumer were collected using snow ball method. The result of the study showed that: (1) organik rice consumption waas influenced by five characteristics of health taste aroma, taste and stability of rice, (2) hedonic price of organik rice was affected by characteristics of colour, tante, sine, after taste, service, health and continuity of rice product, (3) organik rice consumption in city areas of Yogyakarta was influenced by housewife education, jobs, period of organik rice consumption, variety children under five year dummy.Keywords: organik rice, consumption, city strea